Performance Analysis of Flat-Plate and V-groove Solar Air Heater Through CFD Simulation - Desisa, Debela Geneti; Shekata, Gadisa Desa (Center of Biomass & Renewable Energy, Diponegoro University, 2020)
The simplicity of solar flat plate air collector and free availability of solar energy sources attract attention to the optimization of the collector. This study aims to assess the effect of double pass air flow on the performance of flat plate air collectors. The analysis of the performance characteristics of the indirect solar dryer was carried out by CFD simulation with three different smooth, rough and V-grooved surfaces, keeping the lower and lateral collector well insulated and the drying chamber acting as a vertical chimney. The average thermal efficiency of the V-grooved surface, smooth surface, and rough surface is 90%, 78%, and 62% respectively. The total area of the collector is 1.20 × 2.0 = 2.40 m2 with the dimension of drying cabinet width, depth, and height 1200 × 650 × 1000 mm respectively. The pressure drop observed at the entrance to the drying chamber is high in the case of a smooth surface, medium in a rough surface and low in a V-grooved plate which will allow sufficient gas pressure to pass through completely.The air mass flow rate is the most important and effective factor during drying. The humidity of the air, as well as air velocity, is also an important factor in improving the drying rate.